Determining farm surface porcine reproductive and respiratory syndrome virus (PRRSV) contamination through viability RT-qPCR - Claudio Marcello Melini; Amanda Palowski; Declan C. Schroeder; Cesar A. Corzo (PLoS ONE, 2026)
Porcine reproductive and respiratory syndrome (PRRS) continues to be a major threat to U.S. swine industry, as a substantial number of herds become positive and can pose a risk to other nearby farms, especially in post weaning farms as multiple of them may be overseen by one worker. Personnel moving between farms without adequate biosecurity measures, may play a role in viral spread acting as a fomite. The ability to detect and distinguish between the free PRRS virus (PRRSV) genomic RNA vs its genome found in a viable virus form on frequently touched surfaces in growing pig farms was assess in this study. Ten PRRSV positive growing pig farms in the Midwestern U.S. were visited to collect 20 environmental surface samples and eight oral fluids from each one. Environmental samples were analyzed using standard RT-qPCR and viability RT-qPCR, while oral fluids were assessed using the VetMAX™ PRRSV EU & NA v3.0 kit. The virus’ RNA was commonly detected on metal and plastic (non-porous) surfaces (e.g., pig pen top rail, mortality handling equipment’s handle) from all farms, with 80 out of 200 environmental samples testing positive. Viable virus was detected in 48 samples across six farms, with non-porous materials testing positive more frequently. A generalized linear mixed effect model suggested a negative association (OR = 0.005; 95% CI 0.00, 6.82; p-value = 0.18) between the proportion of positive oral fluids and detecting viable virus from sampled surfaces. Agreement between the detection of RNA and viable PRRSV from surface samples using Cohen’s kappa yielded perfect agreement (κ = 1.00) from doorknobs of different locations, to low agreement (κ = 0.29) in the floor of a specific area, among others. These results indicate the presence of viable virus on surfaces that are frequently touched by the farm’s personnel. This study highlights the importance of biosecurity measures applied to the personnel and their potential role of environmental contamination and PRRSV dissemination. The use of viability RT-qPCR to detect viable PRRSV offers a practical tool in field settings to improve biosecurity protocols to reduce indirect transmission of PRRSV in swine production systems.